2021
DOI: 10.3390/ma14226819
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of the Structure, Mechanical, and Tribological Properties of a Mo-Mo2N Nanocomposite Coating Deposited on the Ti6Al4V Alloy by Magnetron Sputtering

Abstract: Mo-Mo2N nanocomposite coating was produced by reactive magnetron sputtering of a molybdenum target, in the atmosphere, of Ar and N2 gases. Coating was deposited on Ti6Al4V titanium alloy. Presented are the results of analysis of the XRD crystal structure, microscopic SEM, TEM and AFM analysis, measurements of hardness, Young’s modulus, and adhesion. Coating consisted of α-Mo phase, constituting the matrix, and γ-Mo2N reinforcing phase, which had columnar structure. The size of crystallite phases averaged 20.4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…Both coatings are characterized by a very good adhesion to substrates. A slightly worse adhesion is presented by CrCN [4] and Mo 2 N [5] coatings.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Both coatings are characterized by a very good adhesion to substrates. A slightly worse adhesion is presented by CrCN [4] and Mo 2 N [5] coatings.…”
Section: Introductionmentioning
confidence: 91%
“…An analysis of the surfaces of the CrN and CrCN monolayer coatings [38] revealed that they had a surface roughness Ra, respectively, of (0.06 ± 0.01) µm and (0.10 ± 0.02) µm, and the CrCN/CrN multilayer coating had an intermediate value of Ra (0.08 ± 0.01) µm. Otherwise, it was with the Mo 2 N/CrN multilayer coating, characterized by a roughness (Ra about 0,09 µm) higher than the coating component: Mo 2 N, with a Ra about 0.04 µm [5]) and CrN, with a Ra about 0.06 µm [38].…”
Section: Macroparticle Statisticsmentioning
confidence: 99%